Beyond Classroom Management and Curriculum: How Learning Innovation Shapes Educational Quality in Islamic Boarding Schools - Sri Wahyuni Sihombing; Hamengkubuwono Hamengkubuwono; Sutarto Sutarto (Journal Evaluation in Education (JEE), 2026)
Purpose of the study: Facing pressures to enhance educational quality in the digital and multicultural era, this study examines the effects of multicultural classroom management, curriculum implementation, and learning innovation on the learning quality of junior high school students in Islamic boarding schools (pesantren). Addressing the limitations of previous research, it proposes an integrative analytical model that simultaneously investigates these three variables. Methodology: Employing a quantitative design, the study involved 148 students from two Indonesian pesantren. Data were collected using a Likert-scale questionnaire and analyzed through multiple linear regression. Main Findings: The findings show that multicultural classroom management and curriculum implementation do not have significant partial effects on learning quality. In contrast, learning innovation is the dominant predictor, significantly enhancing learning quality (β = 0.538, p < 0.001). Collectively, the three variables explain 55.4% of the variance, highlighting the decisive role of pedagogical innovation in the pesantren context. Novelty/Originality of this study: The study’s originality lies in its integrative model that simultaneously examines managerial, curricular, and pedagogical dimensions within the pesantren, a context rarely studied empirically. The practical implication emphasizes the importance of strengthening teachers' pedagogical innovation to enhance learning quality in multicultural and digital educational environments.